A Theoretical Study of Two Novel Concept Systems for Maximum Thermal-Chemical Conversion of Biomass to Hydrogen - Chung, Jacob N. (Frontiers in Energy Research, 2014)
Two concept systems that are based on the thermochemical process of high-temperature steam gasification of lignocellulosic biomass and municipal solid waste are introduced. The primary objectives of the concept systems are 1) to develop the best scientific, engineering, and technology solutions for converting lignocellulosic biomass, as well as agricultural, forest and municipal waste to clean energy (pure hydrogen fuel), and 2) to minimize water consumption and detrimental impacts of energy production on the environment (air pollution and global warming). The production of superheated steam is by hydrogen combustion using recycled hydrogen produced in the first concept system while in the second concept system concentrated solar energy is used for the steam production. A membrane reactor that performs the hydrogen separation and water gas shift reaction is involved in both systems for producing more pure hydrogen and CO2 sequestration. Based on obtaining the maximum hydrogen production rate the hydrogen recycled ratio is around 20% for the hydrogen combustion steam heating system. Combined with pure hydrogen production, both high temperature steam gasification systems potentially possess more than 80% in first law overall system thermodynamic efficiencies.